Peduli Covid-19: Dosen & Mahasiswa Udinus untuk Masyarakat Mranggen - Kusni Ingsih; Anna Sumaryati (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2022)
Limited health facilities and lack of understanding of the community about the Covid-19 virus are one of the problems in dealing with the spread of the Covid-19 virus. To overcome this, the role of academics, namely lecturers and students, is needed to educate the public to reduce the spread of COVID-19 in the Mranggen sub-district. The education provided is in the form of explanations related to the covid-19 virus, how to protect yourself, personal protective equipment used by the community as well as providing motivation to the community for the need to feel safe from physical danger. This activity was carried out by conducting a survey first, providing education to the people of the Mranggen sub-district and distributing personal protective equipment to the Mranggen sub-district community. This activity is important to continue to be carried out to realize the care of academics for the community. Cooperation with other parties such as with private agencies and with the government needs to be carried out so that activities like this can continue to be carried out.